Extensively Drug-Resistant (XDR) Tuberculosis: A Review (BIRDEM Medical Journal, 2012)
Extensively drug-resistant (XDR) tuberculosis is defined as disease caused by Mycobacterium tuberculosis with resistance to at least isoniazid and rifampicin, any fluoroquinolone, and at least one of three injectable secondline drugs (amikacin, capreomycin, or kanamycin). This definition in immensely valuable for more uniform surveillance in varied international settings. The prevalence of tuberculosis drug resistance has risen to the highest rate ever recorded. Although the gold standard for drugsusceptibility testing has been the agar proportion method; due to its time consumption, more sensitive, specific and rapid diagnostic tests are required. It is difficult to differentiate XDR tuberculosis from non-XDR tuberculosis clinically, although the former is associated with greater morbidity and mortality. The treatment of XDR tuberculosis should include agents to which the organism is susceptible, and should continue for a minimum of 18-24 months. However, treatment continues to be limited in tuberculosisendemic countries largely because of weaknesses in national tuberculosis health-care models. The ultimate strategy to control drug-resistant tuberculosis is one that implements a comprehensive approach incorporating innovation from the political, social, economic, and scientific realms. DOI: http://dx.doi.org/10.3329/birdem.v1i1.12386 Birdem Med J 2011; 1(1): 30-36